The Impact of Metabolic Syndrome on Heart Failure in Young Korean Population: A Nationwide Study - Tae-Eun Kim; Do Young Kim; Hyeongsu Kim; Jidong Sung; Duk-Kyung Kim; Myoung-Soon Lee; Seong Woo Han; Hyun-Joong Kim; Hyun Kyun Ki; Sung Hea Kim; Kyu-Hyung Ryu (Metabolites)
Limited data are available regarding the effect of metabolic syndrome on heart failure (HF) development in young individuals. Utilizing data from the Korean National Health Insurance Service, we included a total of 1,958,284 subjects in their 40s who underwent health screening between January 2009 and December 2009 in Korea. Subjects were classified into three groups: normal, pre-metabolic syndrome (Pre-MetS), and metabolic syndrome (MetS). MetS was identified in 10.58% of males and 5.21% of females. The hazard ratio for HF in subjects with MetS was 1.968 (95% CI: 1.526–2.539) for males and 2.398 (95% CI: 1.466–3.923) for females. For those with Pre-MetS, the hazard ratio was 1.607 (95% CI: 1.293–1.997) in males and 1.893 (95% CI: 1.43–2.505) in females. Additionally, acute myocardial infarction and low hemoglobin levels were identified as significant risk factors for HF in both genders. MetS approximately doubled the risk of developing HF in individuals in their 40s. Pre-MetS was also a significant risk factor for HF in this population.